The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/pchj.206
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of premenstrual syndrome: Appraising the effectiveness of cognitive behavioral therapy in addition to calcium supplement plus vitamin D

Abstract: Premenstrual syndrome (PMS) consists of repetitious physical and psychological symptoms. The symptoms occur during the luteal phase of the menstrual period and cease when the menstrual period starts. This study included pre-test and post-test experiments between a control group and a test group. The statistical population involved 40 females, chosen based on multistage cluster sampling. The participants were then divided into four groups to undergo treatment with calcium supplement plus vitamin D together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…Karimi et al [28] investigated the effects of cognitive behavioral therapy (CBT) and calcium plus vitamin D supplementation on the reduction of PMS symptoms. In a trial, Mandana and Azar [31] showed that vitamin E, vitamin B6, calcium, and omega-3 had significant effects on enhancing the physical and mental symptoms of women with PMS.…”
Section: Discussionmentioning
confidence: 99%
“…Karimi et al [28] investigated the effects of cognitive behavioral therapy (CBT) and calcium plus vitamin D supplementation on the reduction of PMS symptoms. In a trial, Mandana and Azar [31] showed that vitamin E, vitamin B6, calcium, and omega-3 had significant effects on enhancing the physical and mental symptoms of women with PMS.…”
Section: Discussionmentioning
confidence: 99%
“…Culture and local research can affect the size of small cause heterogeneity sample sectarian. There needs to be cooperation between counselors, psychologists and doctors in the application of the method in this research [19] V. CONCLUSION Based on literature review that found writer handling PMS in adolescents girls based on based Evidence Based Practice that are: 3. Giving CBT exercise need research long time duration, small cause heterogenitas sample sectarian, and need cooperation between counselor, psychologist and the doctor the.The exercise cbt not effective in the treatment of PMS in adolescents in handling the need to pay attention to and the doses in discharging to effective.…”
Section: Cbt Calcium Supplements Plus Vitamin D To Premenstrual Smentioning
confidence: 99%
“…Therefore, it can increase the quality of life of women in family activity, education, and workplace. CBT implementation has constraints in it culture and the local environment related culture factor could affect CBT [19].…”
Section: Rctmentioning
confidence: 99%
See 2 more Smart Citations